THE ROLE OF BASIC DESIGN COURSE IN THE INTRODUCTION AND DEVELOPMENT OF LOCAL CULTURE VALUES - Purnama Esa Dora; Maria Suzanna G. Poetiray (Jurnal Pendidikan Karakter, 2012)
Abstract: Indonesia has been known as a country which upholds cultural values and philosophy through artworks media. One of those is presented in batik. No other cloth in the Indonesian archipelago, perhaps in the world as well, contains so many symbols and meanings. But sadly, as the globalization emerges, there is a tendency to exalt developed country’s culture, and our young generation no longer cares about our own country’s cultural values. Batik is considered obsolete, not fancy, and only suitable for the old generation. In the modern design world, basic design subject may be a good tool to introduce local values while the young learn to compose the elements and design principles as design sensitivity training. One of the tasks is making a pattern composition using local content, and batik is a complex local pattern that is commonly used as inspiration. Keywords: basic design, local content, batik